2017
DOI: 10.1155/2017/4276928
|View full text |Cite
|
Sign up to set email alerts
|

Culture of iPSCs Derived Pancreatic β-Like Cells In Vitro Using Decellularized Pancreatic Scaffolds: A Preliminary Trial

Abstract: Diabetes mellitus is a disease which has affected 415 million patients in 2015. In an effort to replace the significant demands on transplantation and morbidity associated with transplantation, the production of β-like cells differentiated from induced pluripotent stem cells (iPSCs) was evaluated. This approach is associated with promising decellularized scaffolds with natural extracellular matrix (ECM) and ideal cubic environment that will promote cell growth in vivo. Our efforts focused on combining decellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 44 publications
2
32
0
1
Order By: Relevance
“…In a recently published study from Wan et al, decellularized pancreatic tissues were recellularized with mouse iPSC-derived ß-like cells and cultured for 5 days. Furthermore, the authors showed increased expression of the insulin gene compared to a 2D culture [147]. An as yet neglected point is the importance of the islet niche for recellularization.…”
Section: Pancreasmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recently published study from Wan et al, decellularized pancreatic tissues were recellularized with mouse iPSC-derived ß-like cells and cultured for 5 days. Furthermore, the authors showed increased expression of the insulin gene compared to a 2D culture [147]. An as yet neglected point is the importance of the islet niche for recellularization.…”
Section: Pancreasmentioning
confidence: 97%
“…Only a few publications have examined the decellularization of whole pancreas and the subsequent repopulation with islets of Langerhans. Protocols for perfusion‐based decellularization of the mouse, rat, pig and human pancreas have been published , but use different detergents and times to decellularize the pancreas. Detergents include nonionic tensides such as Triton X‐100 and enzymatic agents such as DNAse.…”
Section: Pancreasmentioning
confidence: 99%
“…Not only do they provide space for cell growth but they also promote cell migration, differentiation, and metabolism through interactions with the cell matrix . In our previous study, we succeeded in recellularizing the decellularized pancreatic scaffold with induced pluripotent stem cell‐derived pancreatic β‐like cells . Unfortunately, vascularization of the engineered tissue remains the main challenge for making engineered pancreatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…22 In our previous study, we succeeded in recellularizing the decellularized pancreatic scaffold with induced pluripotent stem cell-derived pancreatic β-like cells. 23 Unfortunately, vascularization of the engineered tissue remains the main challenge for making engineered pancreatic tissue. It has been shown that the exposed ECM in the vascular network is responsible for platelet activation and formation of a thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus stem cells can be considered a potent and encouraging cell source for tissue engineering [124]. Accordingly to this concept, Wan et al has just proposed a study about the possibility to culturing iPSCs derived pancreatic β cells on decellularized ECM [125]. After peristaltic artery perfusion with detergents, decellularized ECM-based pancreas were seeded with already differentiated into β cells like iPSCs (approx.…”
Section: Small Animal Modelsmentioning
confidence: 99%